Geometry – Construction – Architecture in the treatise delle fortificazioni by Galasso Alghisi - Zerlenga, Ornella; Cirafici, Alessandra (DISEGNARECON, 2012)
This article presents an application of geometry in architecture. It aims to investigate the geometric pattern underlying the conceptual design of the model of Renaissance fortification proposed by Galasso Alghisi in the treatise Delle Fortificationi (Venice 1570). The study focuses on the geometrical analysis of the generative dynamic of the tested form which is illustrated here by means of detailed engravings. More specifically, the following aspects will be examined: the method of the geometric-configurative of the fortification type proposed by Alghisi, together with the identification of the related formal matrices; the functioning of the Istromento (instrument) described by Alghisi and advised in order to proportion the sites to be built upon and transform the drawings of the fortresses into structures following the proportions.